If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -23 = 6r + 12 Reorder the terms: -23 = 12 + 6r Solving -23 = 12 + 6r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-6r' to each side of the equation. -23 + -6r = 12 + 6r + -6r Combine like terms: 6r + -6r = 0 -23 + -6r = 12 + 0 -23 + -6r = 12 Add '23' to each side of the equation. -23 + 23 + -6r = 12 + 23 Combine like terms: -23 + 23 = 0 0 + -6r = 12 + 23 -6r = 12 + 23 Combine like terms: 12 + 23 = 35 -6r = 35 Divide each side by '-6'. r = -5.833333333 Simplifying r = -5.833333333
| 18r+4= | | -23=16r-5 | | 3x^2+2x-x=0 | | 5x+3=37x | | 54=8g+10-4(3g+12) | | 2(2x+40)=180 | | 54=8g+12-4(3g+12) | | 1x+5=10x | | 12-2y=y-6+3y | | 5(9x+13)=7(4x+10) | | -35+7+12-18-1-16= | | 2(6x+14)=7(8x+12) | | 2(x+8)=5(x+11) | | 16=3x-X | | X=27+-1Y | | 6=3y+9 | | 2(x+6)=5(x+12) | | 20-/2=50 | | 1.5x=24 | | 1.5=24 | | 15=300 | | 3p^2-5p+2=y | | ln(X-7)-5=2 | | X+Y+10=37 | | 2/9t=36 | | 3B+4B=24 | | 16-3+-4+2-12+2= | | x^4-tx^2+16=0 | | 121^3/2 | | 10-2f=15-3f | | 5m+4m=27m | | 5y^2+7y-34=0 |